2022
DOI: 10.3389/fphar.2022.778032
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chang-Kang-Fang Formula on the Microbiota-Gut-Brain Axis in Rats With Irritable Bowel Syndrome

Abstract: Chang-Kang-Fang formula (CKF), a multi-herb traditional Chinese medicine, has been used in clinical settings to treat irritable bowel syndrome (IBS). Recent studies show that 5.0 g/kg/d CKF can alleviate the symptoms of IBS rats by modulating the brain-gut axis through the production of brain-gut peptides (BGPs), thus relieving pain, and reversing the effects of intestinal propulsion disorders. However, the exact mechanisms underlying the therapeutic effects of CKF in IBS remain unclear. The microbiota-gut-bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…Clostridium growth was observed in antibiotic-induced irritable bowel syndrome mice, indicating that Clostridium may play a role in colonic motility ( 28 ). A previous study found that the abundance of Clostridiales was increased in rats with irritable bowel syndrome, indicating that the abundance of Clostridiales is possibly related to colonic disorder ( 29 ). In the meantime, reducing the abundance of Clostridiales in the gut can restore GI homeostasis and motility ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clostridium growth was observed in antibiotic-induced irritable bowel syndrome mice, indicating that Clostridium may play a role in colonic motility ( 28 ). A previous study found that the abundance of Clostridiales was increased in rats with irritable bowel syndrome, indicating that the abundance of Clostridiales is possibly related to colonic disorder ( 29 ). In the meantime, reducing the abundance of Clostridiales in the gut can restore GI homeostasis and motility ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found that the abundance of Clostridiales was increased in rats with irritable bowel syndrome, indicating that the abundance of Clostridiales is possibly related to colonic disorder ( 29 ). In the meantime, reducing the abundance of Clostridiales in the gut can restore GI homeostasis and motility ( 29 ). Therefore, we hypothesized that variations in Clostridiales may be associated with diabetic intestinal motility disorder and constipation.…”
Section: Discussionmentioning
confidence: 99%